Painting and Visual Construction in El Ministerio del Tiempo. Las meninas as a study case - Barrientos-Bueno, Mónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
El Ministerio del Tiempo (2015-2020), TV series broadcasted by Spanish National Public Television Channel, uses pictorial tradition to build up characters, past eras and mise-in-scene. This wide and intense use of painting provides a huge visual, aesthetic and storytelling richness in its building of the past. From this point of view, a case study of the recreation of Las meninas is carried out, revealing parallels between Velázquez's conception of his master painting and its audiovisual construction in the TV series.